Analisis Strategi Promosi Penjualan dalam Memanfaatkan Digital Marketing pada Usaha Buket (Studi Kasus di Madehomemade, Ds. Bandung, Kec. Bandung, Kab. Tulungagung) - Nisa’, Rahma Anisa Mirsidatun; Suja’i, Imam Sukwatus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study analyzes the sales promotion strategies utilized by the Madehomemade bouquet business in the use of digital marketing. The focus of this case study is Madehomemade located in Ds. Bandung, Kec. Bandung, Kab. Tulungagung. This study aims to identify effective promotional strategies in utilizing digital marketing as well as the obstacles faced and how the business maintains its existence. The results of the study indicate that the main obstacles in online sales include tight competition on social media that causes consumers to compare prices, as well as unstable internet connection problems and power outages. To maintain the business, Madehomemade focuses on maintaining product quality, innovating in bouquet themes and models, providing fast and friendly responses to consumers, accepting suggestions as evaluations, and always being active on social media.